IMPLEMENTATION OF CORPORATE CRIMINAL RESPONSIBILITY IN LAW ENFORCEMENT OF THE TRANSNATIONAL DIMENSION OF TRAFFICTING IN PERSONS - Reza Mahendra; Zulkarnein Koto; Marsudin Nainggolan (Sekolah Pascasarjana Universitas Swadaya Gunung Jati, 2022)
Trafficking in persons is a modern form of human slavery (Modern Day Slavery) and is one of the worst forms of treatment for violations of human dignity. In this study, the type of research used is normative juridical research with a law approach and a concept approach. From the results of the study, it can be concluded that the use of criminal law regarding corporate criminal liability in the crime of trafficking in persons with a transnational dimension at Unit IV Sub-Directorate III of the Directorate of General Crimes of the Criminal Investigation Unit of the Police is to harmonize the legal arrangements for the criminal act of trafficking in persons charged by the public prosecutor that there are in Article 10 of Law Number 21 of 2007 concerning the Eradication of the Crime of Trafficking in Persons with the theory put forward by experts related to the elements of criminal liability and the model of corporate criminal liability. The implementation of corporate criminal responsibility in law enforcement of the criminal act of trafficking in persons with an effective transnational dimension is one whose solution prioritizes the concept of restorative justice. The concept of restorative justice is the concept of resolving a particular crime that involves all interested parties to jointly seek a solution and at the same time find a solution in dealing with events after the crime has arisen and how to overcome its implications in the future.